A New Soft-Switching Control Technique and Loss Analysis for Parallel Resonant DC-Link Inverter Connected to the Grid - Hakan Donuk; Bilal Gumus (Tehnički Vjesnik, 2022)
This study is recommended to develop a soft-switching control software infrastructure that enables more efficient and effective use of parallel resonant DC link circuits. The fact that the control technique can be easily applied to the soft switching circuit makes it important in this field. With this proposed study, lower voltage ripple and higher efficiency are obtained. To see the results of the technique and to study its effect, a study was carried out on a grid connected inverter. When the frequency changes between 5-15 kHz and 5-10 kW power is transmitted to the grid, the soft switching effect is studied and the efficiency is increased. A software model for calculating the power losses of semiconductor switches has also been established. Using this modeling approach, the power consumption is calculated in detail and the loss analysis is performed using catalog data of semiconductor switches. The accuracy of the obtained results was compared with another simulator. While the PRDCL inverter using the new proposed switching technique transmits 10 kW of power to the grid, the efficiency increased from 97.67% to 98.61% at a switching frequency of 5 kHz, from 96.82% to 98.58% at a switching frequency of 10 kHz, and from 95.61% to 98.55% at a switching frequency of 15 kHz.